2021
DOI: 10.1108/ijse-07-2020-0473
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing ethical judgements of accounting practitioners: some Malaysian evidence

Abstract: PurposeThe purpose of this paper is to examine the extent to which demographic factors and corporate ethical value impact on ethical decisions of Malaysian accounting practitioners.Design/methodology/approachA questionnaire survey was carried out to elicit opinions from accounting practitioners on corporate ethical values and ethical judgements. Regression analysis was performed on 201 completed and useable questionnaires.FindingsThe regression analysis shows that corporate ethical value is a significant facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…No se encontraron estudios en países de Europa y Latinoamérica (ver Cuadro 1). Este resultado, podría relacionarse con lo expuesto por Mohd (2021), quien expone que el Código de Gobierno Corporativo de Malasia recomienda a las empresas el cumpliendo de estándares éticos formalizados para instaurar los valores éticos determinantes para el comportamiento, las decisiones y los juicios éticos de los profesionales contables en las organizaciones, de allí que exista un gran interés por investigar los valores y la cultura ética organizacional para evitar fraudes tributarios.…”
Section: Resultados Y Discusiónunclassified
“…No se encontraron estudios en países de Europa y Latinoamérica (ver Cuadro 1). Este resultado, podría relacionarse con lo expuesto por Mohd (2021), quien expone que el Código de Gobierno Corporativo de Malasia recomienda a las empresas el cumpliendo de estándares éticos formalizados para instaurar los valores éticos determinantes para el comportamiento, las decisiones y los juicios éticos de los profesionales contables en las organizaciones, de allí que exista un gran interés por investigar los valores y la cultura ética organizacional para evitar fraudes tributarios.…”
Section: Resultados Y Discusiónunclassified
“…On the other hand, some studies found that plain-looking male accountants, who represent the traditional accountant stereotype, rarely behave unethically (Shtudiner & Klein, 2020). Ghazali (2021) found that corporate ethical values determine ethical judgement as well as the age of the accountant. This author found that older accounting practitioner is stricter in considering ethical stance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to this call, several studies (Abdelhak, 2019;Adekoya et al, 2020;Mohd Ghazali, 2021;Mustapha and Nadaraja, 2014;Nadaraja and Mustapha, 2017;Odar et al, 2017;West and Buckby, 2020) have in the past examined issues concerning ethical judgement and conduct of accounting professionals. In part, most of these studies have been motivated by the fact that several of the accounting scandals have occurred due to non-observance of ethical standards on the part of accountants.…”
Section: Sbr 164 616mentioning
confidence: 99%